2021
DOI: 10.1038/s41598-020-80274-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel immune prognostic index for stratification of high-risk patients with early breast cancer

Abstract: The prognostic value of current multigene assays for breast cancer is limited to hormone receptor-positive, human epidermal growth factor receptor 2-negative early breast cancer. Despite the prognostic significance of immune response-related genes in breast cancer, immune gene signatures have not been incorporated into most multigene assays. Here, using public gene expression microarray datasets, we classified breast cancer patients into three risk groups according to clinical risk and proliferation risk. We t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Most of these genes had already been reported to be associated with various oncogenic processes, such as JUNB regulating TGFß signaling, invasion, and metastasis [46,47]. PTTG2 has been implicated in glioblastoma tumorigenesis, as well as in head and neck squamous cell carcinoma [36, 48], UTS2 has been reported to possess prognostic value in colorectal and breast cancers [49,50], TRAT1 in early breast cancer prognosis [51] and DUSP1 in sarcoma progression [52]. Of the 32 identi ed genes, nine were found to be associated with basal-like tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these genes had already been reported to be associated with various oncogenic processes, such as JUNB regulating TGFß signaling, invasion, and metastasis [46,47]. PTTG2 has been implicated in glioblastoma tumorigenesis, as well as in head and neck squamous cell carcinoma [36, 48], UTS2 has been reported to possess prognostic value in colorectal and breast cancers [49,50], TRAT1 in early breast cancer prognosis [51] and DUSP1 in sarcoma progression [52]. Of the 32 identi ed genes, nine were found to be associated with basal-like tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is downregulated in LUAD and correlated with poor prognosis ( 61 ). IGHM is an immune-related gene encoding the C region of the µ heavy chain and defines its isoform ( 62 ). It significantly affects the density of infiltrating CD20 + B cells in tumor tissues ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…IL12RB1 has been reported that its mutation played a causal role in non-polyposis CRC pre-disposition. 38 Furthermore, the other three hub genes, IL2RB, XCR1 and CXCR6, have been reported to be related with the prognosis of other cancers, such as early breast cancer, 39 salivary adenoid cystic carcinoma, 40 bladder and hepatocellular cancers. 41,42 Obviously, the subtle quantitative information associated with gene expression would be missed in REO patterns.…”
Section: Discussionmentioning
confidence: 99%